2011
DOI: 10.1007/s11738-011-0774-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture

Abstract: Three experiments were conducted to study the allelopathic stimulation and its underlying molecular mechanism of achyranthes medicinal plants in continuously monoculture system. The stimulators in the rhizospheric soil of continuously monocultured achyranthes plants were extracted by water and organic solvents. Results of the bioassay showed that the rhizospheric soil extracts had a significant promotive effect on the growth of achyranthes in continuous monoculture system, implying that the extracts, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It is reasonable thinking that the current efforts in developing novel perovskite nanostructures will be soon a precious resource in the field of sensors, electronics and energy‐related devices …”
Section: Caesium‐doped Perovskites In Emerging Technologiesmentioning
confidence: 99%
“…It is reasonable thinking that the current efforts in developing novel perovskite nanostructures will be soon a precious resource in the field of sensors, electronics and energy‐related devices …”
Section: Caesium‐doped Perovskites In Emerging Technologiesmentioning
confidence: 99%
“…Li et al (2011) identified 25 differentially expressed proteins in a Chinese medicinal Achyranthes species treated with growth-promoting extracts of soil in which the same species was growing. Proteins associated with stress and secondary plant metabolism, signal transduction, synthesis and degradation of nutritive material, as well as synthesis and degradation of nucleic acids and protein were affected.…”
Section: Proteomicsmentioning
confidence: 99%
“…The rapid development of the portable electronic devices and electric vehicles places increasing demands for advanced batteries with high energy density. [ 1–4 ] However, the energy density of the current intercalation‐based lithium‐ion batteries (LIBs) is approaching to their theoretical energy density values. [ 5 ] Under this circumstance, lithium (Li)‐metal anode has been revived and attracted more and more attention [ 6–9 ] due to its high theoretical capacity (3860 mAh g −1 ) and the lowest reduction potential (−3.04 V vs standard hydrogen electrolyte).…”
Section: Introductionmentioning
confidence: 99%